Life Course and Social Participation: (Not Only) a Question of Fairness - Dabrock, Peter (Justice over the Course of Life, 2022)
A look at the life courses of individuals helps to uncover the grounds and limitations of the justice demanded of others. In doing so we can take a diachronic or synchronic perspective. By diachronic perspective I mean a person’s life course over time. By synchronic perspective I mean the co-existence of different life courses at a certain point in time. The diachronic perspective suggests that justice is grounded in the protection and respect of individual dignity. Accordingly, it has an intrinsic relationship to freedom. The synchronic perspective in turn elucidates that freedom is not possible without the existence, availability and use of a social network created by individuals. If freedom and social participation in the life course rely on each other mutually, then justice represents a necessary but insufficient social obligation to strengthen individuals and foster social cohesion. Precisely those who want to make justice strong need to consider care and solidarity. Later I will argue that solidarity can be understood in terms of giving and gratitude.<br
CRIS-Team WoS Importer:2022-06-10